Praksis Yesus Menafsir Ulang Torah - Fredy Simanjuntak; Eko Prasetyo; Rita Evimalinda (Sekolah Tinggi Teologi Real Batam, 2019)
The Practical Jesus Interpreted the ToraThe central position of the Torah in the Gospels needs to be understood from the way Jesus taught the Torah and the results for establishing the purpose of the Torah. Starting from the response of the scribes or Pharisees interpreted the existence of contradictions in Jesus' ministry regarding the violation of the Torah. Without knowing the context, we cannot know the current debate between Jesus and the scribes and Pharisees. This paper aims to analyze and describe Jesus' actions not as violations but rather than reinterpreting the true Torah.AbstrakPosisi sentral Torah dalam Injil perlu dipahami dari cara Yesus mengajarkan Taurat dan hasil untuk menetapkan maksud Taurat. Bertolak dari tanggapan para ahli taurat atau orang farisi memaknai adanya kontradiksi dalam pelayanan Yesus mengenai pelanggaran Torah. Tanpa mengetahui konteksnya, kita tidak bisa mengetahui perdebatan yang terjadi pada saat itu antara Yesus dengan para ahli taurat dan orang farisi. Tulisan ini Tulisan ini bertujuan untuk menganalisis dan menggambarkan aksi Yesus bukan sebagai pelanggaran tetapi lebih dari kepada menafsir ulang Torah secara utuh.